Informal sector in economic development: An analytical foundation - Bhattacharya, Prabir (UK Palgrave, 2024)
This book bridges the gap between theoretical and empirical understandings of the informal sector to provide insight into the role of the informal sector within the development process. By analysing three economic sectors, it sets out a framework for analysing urbanisation, rural-urban migration, agriculture- industry relationship, income inequality, structural change, employment, and optimal growth. Through highlighting the economic contribution of the informal sector, its impact on the national output and influence on the labour market is shown, alongside how employment opportunities in the informal sector drive rural and urban migration.This book presents a nuanced understanding of the dynamics of the informal sector and its role in the development of economies. It will be of interest to researchers and policymakers working within development economics and growth economics.
Keywords: Informal sector; Urban migration; Development economics